Soil Arthropod Diversity and Composition Inhabited Various Habitats in Universitas Brawijaya Forest in Malang East Java Indonesia - Leksono, Amin Setyo; Putri, Ninda Merisa; Gama, Zulfaidah Penata; Yanuwiyadi, Bagyo; Zairina, Anisa (Journal of Tropical Life Science, 2019)
A study on soil arthropod abundance, diversity and composition have been done on November 2016 to March 2017 using pitfall traps. The objective of this study is to analyze variations of the soil arthropod abundance, diversity and composition among different habitats in a university forest. The study was carried out in Universitas Brawijaya Forest (UBF) Malang, East Java (7°49'S, 112°34'E, 1,200 m in altitude), consisted of four locations: an agroforestry (AF), a gallery forest (GF), the pine stands (PS) and a settlement yard (SY). At each site, a total of 10 traps (5 by 2 rows) were placed systematically at 4-m intervals. Glass cups (10 cm in diameter and 7 cm deep) were buried in the ground during 24 hours. There were 2286 individuals of arthropod collected from all sampling locations. Overall the samples collected consist of 41 families of arthropods. The abundance (mean ± SE) of soil arthropod was highest in PS and the lowest in SY. Statistically, variations in abundance among locations were significant (F = 7.39, p < 0.01). The taxa richness of arthropod was highest in GF and the lowest in SY. Statistically, variations in taxa richness among locations were significant (F = 4.26, p < 0.05). The diversity was the highest in the GF (1.9 ± 0.1) lowest in the SY (0.74 ± 0.1). Statistically, variations in diversity among study sites were significant (F = 26.73, p < 0.001). In general, scavenger dominated the composition of soil arthropods. The highest proportion of scavenger abundance present in SY was 84.9%, while the lowest in the GF was 29.3%. The highest litter transformer composition in GF was 33.9%, and the lowest in SY was 8%. The highest decomposer in PS was 26.9% and the lowest in AF was 12.9%. The highest predator in AF was 20.7% and the lowest in SY was 1%. Compositions of soil arthropod were affected by environmental factors such as soil temperature and light intensity.